2018
DOI: 10.1038/s41598-018-20011-1
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake impacts on microcrustacean communities inhabiting groundwater-fed springs alter species-abundance distribution patterns

Abstract: Earthquakes are important natural events, yet their impacts on animal communities are poorly known. Understanding earthquake impacts on groundwater communities is essential to assess their resilience and hence to perform conservation actions. We investigated how a 6.3 Mw earthquake that occurred in 2009 altered the community structure (diversity, evenness, dominance, species abundance distributions and beta-diversity) of microcrustaceans (Crustacea Copepoda) inhabiting springs fed by the Gran Sasso Aquifer (Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 99 publications
0
11
0
Order By: Relevance
“…Given that these events are increasing in frequency amid the environmental crisis of the new millennium (Rahmstorf & Coumou, 2011), the study of stochastic phenomena has emerged as a central topic in ecology (Scheffer et al ., 2001). Recent papers used groundwater crustaceans to elucidate some of the mechanisms by which earthquakes affect the composition and structure of biological communities (Galassi et al ., 2014; Fattorini et al ., 2017; Fattorini, Di Lorenzo, & Galassi, 2018; Morimura et al ., 2020). Additional studies have focused on the effect of other events, such as heavy precipitation (Calderón‐Gutiérrez, Sánchez‐Ortiz, & Huato‐Soberanis, 2018) and flooding (Pacioglu et al ., 2019).…”
Section: Community Ecologymentioning
confidence: 99%
“…Given that these events are increasing in frequency amid the environmental crisis of the new millennium (Rahmstorf & Coumou, 2011), the study of stochastic phenomena has emerged as a central topic in ecology (Scheffer et al ., 2001). Recent papers used groundwater crustaceans to elucidate some of the mechanisms by which earthquakes affect the composition and structure of biological communities (Galassi et al ., 2014; Fattorini et al ., 2017; Fattorini, Di Lorenzo, & Galassi, 2018; Morimura et al ., 2020). Additional studies have focused on the effect of other events, such as heavy precipitation (Calderón‐Gutiérrez, Sánchez‐Ortiz, & Huato‐Soberanis, 2018) and flooding (Pacioglu et al ., 2019).…”
Section: Community Ecologymentioning
confidence: 99%
“…For instance, the effects of earthquakes on groundwater habitats was recently documented to determine a general reduction of diversity (Galassi et al 2014), variations in abundance patterns (Fattorini et al 2018) and an increase in the spatial niche overlap of previously isolated species (Fattorini et al 2017). For instance, the effects of earthquakes on groundwater habitats was recently documented to determine a general reduction of diversity (Galassi et al 2014), variations in abundance patterns (Fattorini et al 2018) and an increase in the spatial niche overlap of previously isolated species (Fattorini et al 2017).…”
Section: Environmental Stochasticitymentioning
confidence: 99%
“…Taking advantage of local site-specific phenomena, such as earthquakes, floods and volcanic eruptions, a few authors have recently shown that subterranean habitats may actually represent unusual, yet promising systems in which to investigate environmental stochasticity. For instance, the effects of earthquakes on groundwater habitats was recently documented to determine a general reduction of diversity (Galassi et al 2014), variations in abundance patterns (Fattorini et al 2018) and an increase in the spatial niche overlap of previously isolated species (Fattorini et al 2017). Ortuño et al (2013) showed how periodic flooding may extirpate native community in specific subterranean habitats (the so-called 'Alluvial MSS'), enhancing the possibility to use these systems to study re-colonization processes and meta-population dynamics, just like in the famous case of the Krakatau Islands (Thornton et al 1988, Whittaker et al 1989.…”
Section: Environmental Stochasticitymentioning
confidence: 99%
“…Several models have been proposed to describe the SADs (see Whittaker, 2014a,b, 2015;Baldridge et al, 2016;Fattorini et al, 2018). One of the most commonly used models is the so-called log-normal (McGill, 2003).…”
Section: Introductionmentioning
confidence: 99%